Update in Heart Rhythm Abnormalities and Indications for Pacemaker After Transcatheter Aortic Valve Implantation - Saadi, Marina; Tagliari, Ana Paula; Danzmann, Luiz Cláudio; Bartholomay, Eduardo; Kochi, Adriano Nunes; Saadi, Eduardo Keller (Revista brasileira de cirurgia cardiovascular, 2018)
Rhythm abnormalities following transcatheter aortic valve implantation (TAVI) and indications for permanent pacemaker implantation (PPI) were reviewed, which aren't well established in the current guidelines. New left bundle branch block and atrioventricular block are the most common electrocardiographic changes after TAVI. PPI incidence ranges from 9-42% for self-expandable and 2.5-11.5% for balloon expandable devices. Not only anatomical variations in conduction system have an important role in conduction disorders, but different valve characteristics and their relationship with cardiac structures as well. Previous right bundle branch block has been confirmed as one of the most significant predictors for PPI.